ORGANOLEPTIC CHARACTERISTICS AND NUTRITIONAL COMPOSITION OF WHEY-GRAPE JUICE BLENDED BEVERAGE - A. HARIKA, K. LAKSHMI*, G. NIRMALA DEVI and VIMALA BEERA, (The Journal of Research ANGRAU, 2023)
The study was conducted to develop whey and grape juice blended beverage by using whey, grape juice and sugar in the year 2022. Three beverage compositions were prepared: WGB1 (90%Whey:10%GJ), WGB2 (80%Whey:20%GJ) and WGB3 (70%Whey:30%GJ). Five grams of sugar was added to every 100 ml of the beverage. Organoleptic evaluation of the beverages was carried out by 25 semi-trained panel members. A 9- point hedonic scale was used to assess the sensory attributes such as color, appearance, flavor, taste, consistency and overall acceptability. The one-way ANOVA was used to test for significant differences in the mean scores of sensory evaluation. Although all combinations of whey and grape juice were found acceptable, the treatment WGB2 which contained 70 ml whey, 30 ml grape juice and 5 g sugar, received significantly highest mean scores for color (8.19), appearance (7.80), flavor (7.80), taste (7.84), consistency (7.92) and overall acceptability (8.19), which was found superior amongst all the treatments. The results of the nutrient analysis showed that the highly accepted beverage, which is 70:30 whey-grape juice blend contained 90% moisture, 0.64 g ash, 0.81 g protein, 0.41 g fat, 3.28 g lactose and 101.8 mg calcium. These results showed a high potential to produce and develop a new functional whey product.